2023
DOI: 10.1097/pap.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Digestive Tract Histopathologic Findings in the Setting of Severe Acute Respiratory Syndrome Coronavirus-2 Infection: What Pathologists Need to Know

Abstract: Although the novel severe acute respiratory syndrome coronavirus-2 is known primarily to affect the respiratory system, current evidence supports its capability to infect and induce gastrointestinal tract injury. Data describing the histopathologic alterations of the digestive system in patients infected with severe acute respiratory syndrome coronavirus-2 are becoming more detailed, as the number of studies is increasing and the quality of our insight into the infection and the histopathologic findings is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(641 reference statements)
0
1
0
Order By: Relevance
“…[ 20 ] Subsequent reports revealed that ACE2 is significantly expressed in the colonocytes of the colon, the lining enterocytes from the ileum, and the esophageal epithelium. [ 21 ] The discovery of the virus in the GI lumen near its matching receptor provides compelling evidence that COVID-19 can actively replicate, infect, and cause enteric disease, perhaps resulting in fecal transmission. [ 22 ] Moreover, an unexpected finding has also been revealed in that 64% of COVID-19 patients continued to test positive for viral RNA in the feces once the pharyngeal test was showing negative.…”
Section: Gastrointestinal and Covid-19: Pathophysiology And Pathologymentioning
confidence: 99%
“…[ 20 ] Subsequent reports revealed that ACE2 is significantly expressed in the colonocytes of the colon, the lining enterocytes from the ileum, and the esophageal epithelium. [ 21 ] The discovery of the virus in the GI lumen near its matching receptor provides compelling evidence that COVID-19 can actively replicate, infect, and cause enteric disease, perhaps resulting in fecal transmission. [ 22 ] Moreover, an unexpected finding has also been revealed in that 64% of COVID-19 patients continued to test positive for viral RNA in the feces once the pharyngeal test was showing negative.…”
Section: Gastrointestinal and Covid-19: Pathophysiology And Pathologymentioning
confidence: 99%